DIFFERENCES IN THE LEARNING ABILITY OF MALE AND FEMALE STUDENT IN WRITING DESCRIPTIVE SKILLS OF GRADE X STUDENTS OF SMAN 4 KEDIRI - Inge Aprilia Saputri; Rika Riwayatiningsih; Dewi Kencanawati (Media Inovasi Pendidikan dan Pembelajaran, 2023)
This study aims to determine differences in the ability to write descriptive text. From male students to female students, students of class X SMAN 4 Kediri. This type of research is quantitative because it collects data using numbers. The sample class studied was one, namely class X-1, which consisted of 30 people, 13 male and 17 female. The research instrument used was a written test given to students when collecting the data. The results of the research show that the ability to write descriptive text among class X students at SMAN 4 Kediri, namely between male and female students, is indeed different. Based on the average calculation, male students got a score of 43.0763 (44) while the average score for female students was 65.1765 (66). So it can be concluded that the difference in their writing abilities is significant; this can be seen from the SPSS calculation results from the independent t-test.